Macroglossia secondary to lymphangioma of the deep neck space: Report of two cases - Han-Gil Cho; Soo-Young Kim; Eun-Song Song; Joon-Kyoo Lee; Young-Youn Choi (Korean Pediatric Society, 2010)
Lymphangioma is a rare, benign, and hamartomatous tumor of the lymphatic vessels that shows a marked predilection for the head and neck region. When this tumor occurs on the tongue or mouth floor or in the deep neck space, blockage of the efferent lymphatic vessels can result in secondary macroglossia. We report here two patients who showed unusual macroglossia from birth. Initially, there was no noticeable cervical or mandibular swelling. However, mandibular swellings were noted during follow-up examinations, which led to MRI scans on the two infant patients at 5 months and 5 weeks of age, respectively. Subsequently, both patients were diagnosed with lymphangioma or lymphangiohemangioma in the deep neck space.